Gravity Model to Understand China International Trade: A Review Literature - Ahmad Anwar Anwar; Agung Wicaksono (VALUTA, 2022)
Since its development, the gravity model of international trade has received some critics. However, there have been continuously studies using the model. This paper is a literature review by evaluating some scholarly works that analyse China's trajectory in doing its international trades. China is taken as a case study for the empirical course since the country has been maintaining its international trade with many countries. By doing so, this paper maintains that the gravity model still meets its relevance to understanding international trade patterns. It should also be noted that most studies use an augmented gravity model instead of the traditional one.